Data for development: The case for Africa. Issue 1 (18th October 2019) - Assefa, Shimelis; Alemneh, Daniel Gelaw; Rorissa, Abebe
ABSTRACT: This study presents the results of a systematic review of data use practices by African countries to support the United Nations Sustainable Development Goals (UN SDGs) #2 – agriculture. Data use practices and existing data infrastructure are reviewed through the lens of the four big data value‐chain ‐ data generation, data acquisition, data storage, and data analysis. The findings show that – 1) national statistical offices are the primary institutions responsible for data collection and analysis at country level; 2) survey is the primary means for data generation and acquisition; c) the capability to transform data into actionable insight and knowledge is severely limited; 4) data is heavily used for reporting purposes.